Study of Mechanical Properties on Hollow Core Wall Panel (HCWP) in The Precast Concrete System - Ahmad Rizal, Ahmad Hilman; Abdul Ghani, Abdul Halim (Recent Trends in Civil Engineering and Built Environment, 2024)
Hollow Core Wall Panel (HCWP) is one of the partition walls commonly used in the construction industries in Malaysia since the conventional method have many lacks in vary aspect such as increasing the material and labour demands, quality of construction, cost of project and time management. Hence, the objective of this study is to investigate compressive strength between HCWP and Normal Brick Wall (NBW) and to study on flexural strength between HCWP and NBW where HCWP samples collected at ACOTEC Sdn. Bhd. factory at Johor, Malaysia. By using three samples of HCWP and three samples of NBW for compressive and three-point bending test, the compressive and flexural of wall samples can be compared due to its mechanical properties. Thus, the result of this study shows the compressive test data that initiates the strength of wall samples as non-load bearing and the deformation and cracking from flexural test that justified the wall samples to resist load from the structure members. From the analysis that has been done, HCWP have higher compressive strength than NBW but in term of flexural strength, HCWP have lower strength compared to NBW. It shows that HCWP cannot support directly other structure members as it has low flexural strength.